Thermal and mechanical properties of mortars reinforced with recycled brass fibres. (17th May 2021) - Borinaga-Treviño, R.; Orbe, A.; Canales, J.; Norambuena-Contreras, J.
Highlights: Recycled brass fibres from electrical discharge machining were used in mortars. 10 mm long fibres did not alter mortar consistency, but 15 mm and 25 mm decreased it significantly. Longer fibres and higher fibre proportions increased the thermal conductivity of the mortars. Mechanical properties were significantly improved with 15 mm and 25 mm long fibres. Abstract: This paper aims to encourage the circular economy and merge the manufacturing and the construction industries, providing waste fibres from the electrical discharge machining of the former as raw material for the latter. The research analyses the effect on the physical, thermal and mechanical properties of mortars reinforced with brass fibres. The manuscript deals with different fibre length (10 mm, 15 mm and 25 mm) in variable percentages (0.5%, 1%, 2% and 4%). Larger amounts and longer fibres tend to increase the thermal conductivity whereas post cracking flexural strength is more dependent on fibre length.